The dragonmaster's revenge : an unofficial graphic novel for Minecrafters - Stevens, Cara J. (Stevens, Cara J. Battle station prime, 2021)
The skeleton armies are gone, trading is a breeze, and life is somewhat normal for the kids who decided to stay at the outpost. They know it's only a matter of time before the Dragonmaster seeks revenge over the Ender Dragon egg.